Identifying the Public’s Psychological Concerns in Response to COVID-19 Risk Messages in Singapore (Journal of International Crisis and Risk Communication Research, 2021)
Understanding the social-psychological processes that characterize communities’ reactions to a pandemic is the first step toward formulating risk communications that can lead to better health outcomes. This study examines comments on Facebook pages of five Singapore media outlets to understand what topics are being discussed by the public in reaction to the implemented precautionary measures in Singapore so as to infer their psychological concerns. Using Anchored Correlation Explanation as a topic modelling technique, this study examines around 10,000 comments and identifies 21 topics that are discussed. The 21 topics were categorized and organized into seven broad themes of psychological concerns. Implications for theory and practice are then discussed.